Pedagogical Conditions of Professional Interaction of the Social Pedagogue of Educational Institution - Tetiana Ostrianko (Pedagogical Discourse, 2013)
In article the importance and need of interaction of the social pedagogue with pedagogical collective in the course of socialization of pupils is noted. The author focused attention on definition and justification of pedagogical conditions which would promote ensuring professional interaction of the social pedagogue with secondary school administration, the practical psychologist, teachers, and parents. Offers on studying the practical ways of social pedagogue interaction with the practical psychologist, administration and teachers in educational institution, and also definition of levels of professional interaction of the specialist in the course of realization of social and pedagogical activity were made.